Antipinite, KNa3Cu2(C2O4)4, a new mineral species from a guano deposit at Pabellón de Pica, Chile. (2nd January 2018) - Chukanov, Nikita V.; Aksenov, Sergey M.; Rastsvetaeva, Ramiza K.; Lyssenko, Konstantin A.; Belakovskiy, Dmitriy I.; Färber, Gunnar; Möhn, Gerhard; Van, Konstantin V.
Abstract: The new oxalate mineral antipinite is found in a guano deposit located on the Pabellón de Pica Mountain, Iquique Province, Tarapacá Region, Chile. Associated minerals are halite, salammoniac, chanabayaite, joanneumite and clays. Antipinite occurs as blue, imperfect, short prismatic crystals up to 0.1 mm × 0.1 mm × 0.15 mm in size, as well as their clusters and random aggregates. The mineral is brittle. Mohs hardness is 2; D meas = 2.53(3), D calc = 2.549 g cm –3 . The infrared spectrum shows the presence of oxalate anions and the absence of absorptions associated with H2 O molecules, C–H bonds, CO3 2–, NO3 – and OH – ions. Antipinite is optically biaxial (+), α = 1.432(3), β = 1.530(1), γ = 1.698(5), 2Vmeas = 75(10)°, 2Vcalc = 82°. The chemical composition (electron-microprobe data, C measured by gas chromatography of products of ignition at 1200°C, wt.%) is Na2 O 15.95, K2 O 5.65, CuO 27.34, C2 O3 48.64, total 99.58. The empirical formula is K0.96 Na3.04 Cu2.03 (C2.00 O4 )4 and the idealized formula is KNa3 Cu2 (C2 O4 )4 . The crystal structure was solved and refined to R = 0.033 based upon 4085 unique reflections with I > 2σ( I ). Antipinite is triclinic, space group P 1, a = 7.1574(5), b = 10.7099(8), c = 11.1320(8) Å, α = 113.093(1), β = 101.294(1), γ = 90.335 (1)°, V = 766.51(3) Å 3, Z = 2. The strongest reflections of the powder X-ray diffraction pattern [ d, Å ( I, %) ( hkl )] are 5.22 (40) (111), 3.47 (100) (032), 3.39 (80) (210), 3.01 (30) (033, 220), 2.543 (40) (122, 034, 104), 2.481 (30) (213), 2.315 (30) (143, 310), 1.629 (30) (146, 414, 243, 160).